2019
DOI: 10.1016/j.neulet.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal lysosomes

Abstract: Lysosomes support diverse cellular functions by acting as sites of macromolecule degradation and nutrient recycling. The degradative abilities of lysosomes are conferred by a lumen that is characterized by an acidic pH and which contains numerous hydrolases that support the breakdown of major cellular macromolecules to yield cellular building blocks (amino acids, nucleic acids, sugars, lipids and metals) that are transported into the cytoplasm for their re-use. In addition to these important hydrolytic and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 127 publications
(148 reference statements)
0
65
0
Order By: Relevance
“…This is in line with data from the in vitro GVB model that consistently shows a LAMP1/LIMP2-positive GVB membrane, but a range of CTSD and DQ-BSA intensity values in the population of GVBs [143], which could indicate variation in the degradative capacity between individual GVBs. The predominant somatic localization of GVBs mimics the subcellular distribution of proteolytically active lysosomes in neurons that are more abundant in the soma than the neuronal protrusions in contrast to earlier organelles in the endo-and autolysosomal pathways [28,150]. In conclusion, combined post-mortem and experimental data showing a single limiting membrane, the presence of lysosomal membrane and proteolytic proteins as well as degradative capacity therefore identify GVBs as active lysosomal structures, rather than autophagosomes.…”
Section: Gvb Identitymentioning
confidence: 64%
“…This is in line with data from the in vitro GVB model that consistently shows a LAMP1/LIMP2-positive GVB membrane, but a range of CTSD and DQ-BSA intensity values in the population of GVBs [143], which could indicate variation in the degradative capacity between individual GVBs. The predominant somatic localization of GVBs mimics the subcellular distribution of proteolytically active lysosomes in neurons that are more abundant in the soma than the neuronal protrusions in contrast to earlier organelles in the endo-and autolysosomal pathways [28,150]. In conclusion, combined post-mortem and experimental data showing a single limiting membrane, the presence of lysosomal membrane and proteolytic proteins as well as degradative capacity therefore identify GVBs as active lysosomal structures, rather than autophagosomes.…”
Section: Gvb Identitymentioning
confidence: 64%
“…Hydrolytic enzymes capable of degrading macromolecules and cell components were contained in lysosomes, which are cytoplasmic membrane-enclosed organelles. Previous studies have shown the role of lysosome dysfunction in neurodegenerative diseases (Ferguson, 2018a,b). We also found the possible involvement of plasma 27-OHC increase in disorders of lysosome function and cholesterol metabolism in brain tissues of rats (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lysosomes are membrane-bound, acidic organelles that are primarily involved in intracellular degradation of biomacromolecules but also participate in various non-degradative processes such as nutrient and growth factor signaling and plasma membrane repair ( Ballabio and Bonifacino, 2020 ). Axonal lysosomes are particularly heterogeneous with regard to their degradative capacity and acidity ( Lee et al, 2011 ; Gowrishankar et al, 2015 ; FarĂ­as et al, 2017 ; Cheng et al, 2018 ; Farfel-Becker et al, 2019 ), a property that may reflect the existence of populations of lysosomes with distinct functions or maturational states ( Ferguson, 2019 ). In mammals, anterograde lysosome transport depends on coupling to several members of the kinesin family, especially the kinesin-1 proteins KIF5A, KIF5B, and KIF5C, and kinesin-3 proteins KIF1A and KIF1Bβ ( Nakata and Hirokawa, 1995 ; Tanaka et al, 1998 ; Matsushita et al, 2004 ; Guardia et al, 2016 ; FarĂ­as et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%